Pengaruh Nilai Hedonis Dan Nilai Utilitarian Terhadap Behavioral Intention, Dengan Word Of Mouth (Wom) Sebagai Variabel Mediasi - Windah Estrilia Somba; Sunaryo Sunaryo; Mugiono Mugiono (Jurnal Manajemen dan Kewirausahaan, 2018)
The purpose of this study is to analyze the direct and indirect effect of hedonic value, utilitarian value, word of mouth, and behavioral intention of consumer in Casa Baio Paradise Resort, Sulawesi Utara. This study uses questionnaires as the research instrument with 108 respondents as the sample. Sampling technique is purposive sampling. This study uses Partial Least Square (PLS) to analyzed the data. The result shows that there are : 1) a significant direct effect of hedonic value to word of mouth; 2) utilitarian value to word of mouth; 3) utilitarian value and word of mouth to behavioral intention. This study also confirm that word of mouth full mediates the influence of hedonic value to behavioral intention and partial mediates the influence of utilitarian value to behavioral intention. The other result shows that there is no significant relationship between hedonic value and behavioral intention.  https://doi.org/10.26905/jmdk.v6i1.2071